Is death our business? Philosophical conflicts over the end-of-life in old age psychiatry. (2nd June 2016) - McKellar, Duncan; Ng, Felicity; Chur-Hansen, Anna
Abstract : Objectives: Old age psychiatrists work with end-of-life (EOL) issues and encounter patient deaths, but death and dying have received limited focus in old age psychiatry training and research. This qualitative study explores old age psychiatrists' experience of and approach to working with patients at the EOL. Method: Australian old age psychiatrists were purposively sampled and interviewed in-depth. Data saturation was achieved after nine participant interviews. Verbatim transcripts were analysed for themes, which were independently verified. Results: Two dichotomous overarching themes were identified. Death is not our business reflected participants' experience of working in a mental health framework and incorporated four themes: death should not occur in psychiatry; working in a psychiatric treatment model; keeping a distance from death and unexpected death is a negative experience. Death is our business reflected participants' experience of working in an aged care context and incorporated four themes: death is part of life; encountering the EOL through dementia care; doing EOL work and expected death is a positive experience. Conclusion: Participants reported conflict because of the contradictory domains in which they work. They were comfortable working with patients at the EOL when death was expected, particularly in dementia. By contrast, they struggled with death as an adverse outcome in circumstances influenced by mental health culture, which was characterised by risk management, suicide prevention and a focus on recovery. This study has implications for models of care underpinning old age psychiatry. An integrated person-centred model of care may provide a contextually appropriate approach for practice.